Optical glass, glass materials for press molding, optical element blanks and optical elements
By optimizing the cation ratios in the glass composition, the optical glass achieves a high refractive index and low dispersion while minimizing expensive components, addressing the cost issue of existing high refractive index low dispersion glass.
Patent Information
- Application Number
- JP2024043068
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-03-19
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2038-10-11
AI Technical Summary
The high refractive index low dispersion glass described in Patent Document 1 is expensive due to its high content of costly glass components like Ta, and there is a need to reduce the proportion of these expensive components to lower the cost of optical elements.
The optical glass composition is optimized by adjusting the cation ratios of Ta, Ti, Nb, W, Bi, La, Gd, Y, Mg, Ca, Sr, Ba, Zn, Si, and B to achieve a high refractive index and low dispersion while minimizing the content of expensive components, such as Ta, Gd, Nb, and W.
This approach results in an optical glass with a refractive index in the range of 1.9000 to 2.1500 and an Abbe number in the range of 20.0 to 35.0, suitable for optical elements, while reducing production costs by lowering the proportion of expensive glass components.
Smart Images

Figure 0007663736000001 
Figure 0007663736000002 
Figure 0007663736000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical glass, a glass material for press molding, an optical element blank, and an optical element. [Background technology]
[0002] Optical glass having a high refractive index and low dispersion (high refractive index, low dispersion glass) is useful as a material for optical elements. Such high refractive index, low dispersion glass is disclosed in Patent Document 1, for example. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2009-203155 A Summary of the Invention [Problem to be solved by the invention]
[0004] High-refractive-index, low-dispersion glass as disclosed in Patent Document 1 can correct chromatic aberration while enabling the optical system to be made compact by combining a lens made of this glass with a lens made of extra-low dispersion glass or the like to form a cemented lens. However, the optical glass described in Patent Document 1 contains a large amount of a relatively expensive component (e.g., Ta2O5) among various glass components. However, in order to enable the cost reduction of optical elements made of high refractive index, low dispersion glass, it is desirable to reduce the proportion of expensive glass components in the glass composition of the optical glass.
[0005] One aspect of the present invention provides an optical glass that has a low proportion of expensive glass components in its glass composition, a high refractive index, and low dispersion. [Means for solving the problem]
[0006] One aspect of the present invention is In the glass composition expressed in cation percentage, Ta 5+ The content is in the range of 0 to 5 cationic percent, Ti 4+ , Nb 5+ , W 6+ and Bi 3+ Ti content relative to the total content 4+ Cation ratio of content (Ti 4+ / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ ) is in the range of 0.60 to 1.00, La 3+ , Gd 3+ and Y 3+ Si content relative to the total content 4+ and B 3+ The cation ratio of the total content of (Si 4+ +B 3+ ) / (La 3+ +Gd 3+ +Y 3+ ) is in the range of 0.30 to 2.40, Ti 4+ , Nb 5+ , W 6+ and Bi 3+ Si content relative to the total content 4+ and B 3+ The cation ratio of the total content of (Si 4+ +B 3+ ) / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ )) is in the range of 0.30 to 34.00, Ti 4+ , Nb 5+ , W 6+ and Bi 3+ La relative to the total content 3+ , Gd 3+ and Y 3+ The cation ratio of the total content of (La 3+ +Gd 3+ +Y 3+ ) / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+)) is in the range of 0.30 to 33.00, La 3+ and Y 3+ and Mg content 2+ , Ca 2+ , Sr 2+ , B.A. 2+ and Zn 2+ The cation ratio of the total content ((Mg 2+ +Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) / (La 3+ +Y 3+ )) is in the range of 0.00 to 1.50, S 4+ and B 3+ and Mg content 2+ , Ca 2+ , Sr 2+ , B.A. 2+ and Zn 2+ Cation ratio ((Mg 2+ +Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) / (Si 4+ +B 3+ )) is in the range of 0.00 to 1.00, S 4+ , B 3+ , Zn 2+ , La 3+ , Y 3+ , Zr 4+ and Ti 4+ Gd content relative to the total 3+ , Nb 5+ and W 6+ The cation ratio of the total content of (Gd 3+ +Nb 5+ +W 6+ ) / (Si 4+ +B 3+ +Zn 2+ +La 3+ +Y 3+ +Zr 4+ +Ti 4+ )) is in the range of 0.000 to 0.100, an optical glass having a refractive index nd in the range of 1.9000 to 2.1500 and an Abbe number νd in the range of 20.0 to 35.0; Regarding.
[0007] Among the raw materials for optical glass, Ta compounds, Gd compounds, Nb compounds and W compounds are relatively expensive. 5+ The content is controlled within the above range. 3+ , Nb 5+ and W 6+ The proportion of Gd 3+ , Nb 5+ and W 6+ Regarding the cation ratio (Gd 3+ +Nb 5+ +W 6+ ) / (Si 4+ +B 3+ +Zn 2+ +La 3+ +Y 3+ +Zr 4+ +Ti 4+ In other words, in the glass composition of the optical glass, Ta, which is an expensive glass component, is within the above range. 5+ , Gd 3+ , Nb 5+ and W 6+ In such a glass composition, by adjusting the glass composition so as to satisfy the various cation ratios described above, it is possible to obtain an optical glass having a high refractive index nd within the above range and an Abbe number vd (i.e., low dispersion) within the above range. Effect of the Invention
[0008] According to one aspect of the present invention, it is possible to provide an optical glass that has optical properties (nd and νd) useful as a material for optical elements and can contribute to reducing the cost of optical elements. According to another aspect, it is possible to provide an optical glass that further has one or more physical properties of high glass stability, low specific gravity, and low coloration (high transmittance). Furthermore, according to another aspect of the present invention, it is possible to provide a press molding glass material, an optical element blank, and an optical element made of the optical glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] [Optical glass] In the present invention and this specification, the content and total content of cationic components are expressed in cationic % unless otherwise specified, and the content and total content of anionic components are expressed in anionic % unless otherwise specified. Here, "cation %" is a value calculated by "(number of cations of interest / total number of cations in glass components) x 100" and means the molar percentage of the amount of cations of interest relative to the total amount of cationic components. Furthermore, "anion %" is a value calculated by "(number of anions of interest / total number of anions in glass components) x 100" and means the molar percentage of the amount of the anion of interest relative to the total amount of the anion components. The molar ratio of the contents of the cationic components to each other is equal to the ratio of the contents of the cationic components of interest expressed in cationic %; the molar ratio of the contents of the anionic components of interest is equal to the ratio of the contents of the anionic components of interest expressed in anionic %. The molar ratio of the content of a cationic component to the content of an anionic component is the ratio of the contents (expressed in mol %) of the components of interest when the total amount of all cationic components and all anionic components is 100 mol %. The content of each component can be quantified by known methods, such as inductively coupled plasma atomic emission spectrometry (ICP-AES), inductively coupled plasma mass spectrometry (ICP-MS), ion chromatography, and the like. In the present invention and this specification, the content of a component being 0% or not being contained or not being introduced means that the component is substantially not contained, and the content of the component is at or below the impurity level. At or below the impurity level means, for example, less than 0.01%.
[0010] The optical glass (sometimes simply referred to as "glass") will be described in more detail below.
[0011] <Glass composition> The optical glass is Ta 5+ Ta, an expensive glass component with a content of 0-5 cationic %. 5+ From the viewpoint of further reducing the cost of optical elements, Ta 5+ The content is preferably 4% or less, more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 5+ It is even more preferable that it does not contain
[0012] In the above optical glass, Si 4+ , B 3+ , Zn 2+ , La 3+ , Y 3+ , Zr 4+ and Ti 4+ Gd content relative to the total 3+ , Nb 5+ and W 6+ The cation ratio of the total content of (Gd 3+ +Nb 5+ +W 6+ ) / (Si 4+ +B 3+ +Zn 2+ +La 3+ +Y 3+ +Zr 4+ +Ti 4+ )) is in the range of 0.000 to 0.100. That is, the above optical glass has a Gd 3+ , Nb 5+ and W 6+From the viewpoint of further reducing the cost of optical elements, the above cation ratio ((Gd 3+ +Nb 5+ +W 6+ ) / (Si 4+ +B 3+ +Zn 2+ +La 3+ +Y 3+ +Zr 4+ +Ti 4+ )) is preferably 0.090 or less, more preferably 0.080 or less, even more preferably 0.070 or less, even more preferably 0.060 or less, even more preferably 0.050 or less, even more preferably 0.040 or less, even more preferably 0.030 or less, even more preferably 0.025 or less, 0.020 or less, 0.015 or less, 0.010 or less, 0.007 or less, 0.005 or less, 0.004 or less, 0.003 or less, 0.002 or less, or 0.001 or less, and even more preferably 0.000. That is, Gd 3+ , Nb 5+ and W 6+ It is even more preferred that it does not contain
[0013] In the above optical glass, Gd 3+ and W 6+ The total content of Gd 3+ +W 6+ From the viewpoint of reducing the cost of optical elements and reducing the specific gravity of glass, the total content (Gd 3+ +W 6+ ) can be 0% or more, and is particularly preferably 0%.
[0014] In the above optical glass, Si 4+ , B 3+ , Zn 2+ , La 3+ , Y3+ , Zr 4+ and Ti 4+ Gd content relative to the total 3+ and W 6+ The cation ratio of the total content of (Gd 3+ +W 6+ ) / (Si 4+ +B 3+ +Zn 2+ +La 3+ +Y 3+ +Zr 4+ +Ti 4+ From the viewpoint of further reducing the cost of optical elements and the viewpoint of reducing the specific gravity of glass, the above cation ratio ((Gd 3+ +W 6+ ) / (Si 4+ +B 3+ +Zn 2+ +La 3+ +Y 3+ +Zr 4+ +Ti 4+ )) is preferably 0.070 or less, more preferably 0.060 or less, even more preferably 0.050 or less, even more preferably 0.045 or less, even more preferably 0.040 or less, even more preferably 0.035 or less, even more preferably 0.030 or less, even more preferably 0.025 or less, even more preferably 0.020 or less, even more preferably 0.015 or less, even more preferably 0.010 or less, particularly preferably 0.007 or less, especially preferably 0.005 or less, especially preferably 0.004 or less, especially preferably 0.003 or less, especially preferably 0.002 or less, especially more preferably 0.001 or less. The cation ratio ((Gd 3+ +W 6+ ) / (Si 4+ +B 3+ +Zn 2+ +La 3+ +Y 3+ +Zr 4+ +Ti 4+) is particularly preferably 0.000. That is, the optical glass is 3+ and W 6+ It is particularly preferred that it does not contain
[0015] S 4+ and B. 3+ is a glass network forming component. 4+ and B 3+ The total content of 4+ +B 3+ From the viewpoint of enhancing the glass stability, the total content (Si 4+ +B 3+ ) is preferably 55% or less, more preferably 45% or less, even more preferably 40% or less, even more preferably 37% or less, even more preferably 35% or less, and even more preferably 34% or less.
[0016] From the viewpoint of further increasing the glass stability of the above-mentioned optical glass, which is a high refractive index, low dispersion glass, and from the viewpoint of further increasing the refractive index, Si 4+ and B 3+ B relative to the total content of 3+ Cation content ratio (B 3+ / (Si 4+ +B 3+)) is preferably 0.20 or more, more preferably 0.30 or more, even more preferably 0.40 or more, even more preferably 0.50 or more, even more preferably 0.55 or more, even more preferably 0.60 or more, even more preferably 0.61 or more, even more preferably 0.62 or more, even more preferably 0.63 or more, even more preferably 0.64 or more, and even more preferably 0.65 or more. From the same viewpoint, the cation ratio (B 3+ / (Si 4+ +B 3+ The cation ratio (B) is preferably 0.95 or less, more preferably 0.90 or less, even more preferably 0.85 or less, even more preferably 0.83 or less, even more preferably 0.80 or less, even more preferably 0.79 or less, even more preferably 0.78 or less, even more preferably 0.77 or less, even more preferably 0.76 or less, and even more preferably 0.75 or less. 3+ / (Si 4+ +B 3+ It is preferable from the viewpoint of improving the melting property of the glass that the cation ratio (B 3+ / (Si 4+ +B 3+ It is also preferable for the above cation ratio (B 3+ / (Si 4+ +B 3+ ) being not more than the above-exemplified upper limit is preferable from the viewpoint of reducing fluctuations in the glass composition due to volatilization during melting and the resulting fluctuations in the optical properties, from the viewpoint of improving one or more of the chemical durability, weather resistance, and machinability of the glass, and from the viewpoint of reducing coloration.
[0017] Silicon, a glass network forming component 4+ and B 3+ The total content of Si and4+ Content and B 3+ With regard to each content, from the viewpoints of improving the stability, meltability, formability, chemical durability, weather resistance, machinability, etc. of the glass and from the viewpoints of reducing coloring, the preferred ranges are as follows: S 4+ The content is preferably 2% or more, more preferably 3% or more, even more preferably 4% or more, even more preferably 5% or more, even more preferably 6% or more, and even more preferably 7% or more. 4+ The content is preferably 20% or less, more preferably 18% or less, even more preferably 16% or less, even more preferably 14% or less, and even more preferably 12% or less. B 3+ The content is preferably 10% or more, more preferably 15% or more, even more preferably 16% or more, even more preferably 17% or more, even more preferably 18% or more, and even more preferably 19% or more. 3+ The content is preferably 40% or less, more preferably 40% or less, even more preferably 35% or less, even more preferably 30% or less, even more preferably 26% or less, even more preferably 25% or less, even more preferably 24% or less, and even more preferably 23% or less.
[0018] La 3+ , Gd 3+ and Y 3 are components that have the function of increasing the refractive index while suppressing the decrease in the Abbe number. These components also have the function of improving the chemical durability and / or weather resistance of the glass and increasing the glass transition temperature. La 3+ , Gd 3+ and Y 3+ The total content of La 3+ +Gd 3+ +Y 3+From the viewpoint of suppressing a decrease in the refractive index, the above total content (La ) is preferably 20% or more, more preferably 22% or more, even more preferably 24% or more, even more preferably 26% or more, even more preferably 28% or more, even more preferably 30% or more, even more preferably 32% or more, even more preferably 33% or more, even more preferably 34% or more, even more preferably 35% or more, and even more preferably 36% or more. Furthermore, from the viewpoint of suppressing a decrease in the chemical durability and / or weather resistance of the glass and from the viewpoint of suppressing a decrease in the glass transition temperature, the above total content (La 3+ +Gd 3+ +Y 3+ ) is preferably equal to or greater than the lower limit exemplified above. If the glass transition temperature is lowered, the glass becomes more susceptible to breakage when mechanically processing the glass (cutting, machining, grinding, polishing, etc.) (deterioration in machinability). Therefore, suppressing the decrease in the glass transition temperature leads to improved machinability. 3+ +Gd 3+ +Y 3+ ) is preferably equal to or greater than the lower limit exemplified above from the above viewpoints. On the other hand, the total content (La 3+ +Gd 3+ +Y 3+ ) is preferably 60% or less, more preferably 55% or less, even more preferably 50% or less, still more preferably 47% or less, even more preferably 45% or less, even more preferably 44% or less, even more preferably 43% or less, even more preferably 42% or less, even more preferably 41% or less, even more preferably 40% or less, and even more preferably 39% or less, from the viewpoint of enhancing glass stability.
[0019] From the viewpoint of enhancing the glass stability and lowering the specific gravity, the above optical glass contains La 3+ , Gd 3+ and Y 3+The total content of Si, a glass network forming component, 4+ and B 3+ The cation ratio of the total content of (Si 4+ +B 3+ ) / (La 3+ +Gd 3+ +Y 3+ )) is 0.30 or more, preferably 0.50 or more, more preferably 0.60 or more, even more preferably 0.65 or more, even more preferably 0.70 or more, even more preferably 0.75 or more, even more preferably 0.77 or more, even more preferably 0.79 or more, and even more preferably 0.80 or more. The above cation ratio ((Si 4+ +B 3+ ) / (La 3+ +Gd 3+ +Y 3+ )) is, from the viewpoint of achieving a high refractive index, 2.40 or less, preferably 2.00 or less, more preferably 1.50 or less, even more preferably 1.30 or less, even more preferably 1.10 or less, even more preferably 1.05 or less, even more preferably 1.00 or less, even more preferably 0.95 or less, even more preferably 0.94 or less, even more preferably 0.93 or less, even more preferably 0.92 or less, even more preferably 0.91 or less, and particularly preferably 0.90 or less.
[0020] La 3+ , Gd 3+ and Y 3+ Regarding the content of each component, the preferred ranges are as follows: La 3+The content is preferably 20% or more, more preferably 21% or more, even more preferably 22% or more, even more preferably 23% or more, even more preferably 24% or more, even more preferably 25% or more, even more preferably 26% or more, and even more preferably 27% or more. 3+ The content is preferably 60% or less, more preferably 57% or less, even more preferably 55% or less, even more preferably 53% or less, even more preferably 50% or less, even more preferably 47% or less, even more preferably 45% or less, even more preferably 43% or less, even more preferably 40% or less, even more preferably 37% or less, even more preferably 35% or less, particularly preferably 34% or less, especially more preferably 33% or less, especially more preferably 32% or less, especially more preferably 31% or less, especially more preferably 30% or less, and especially more preferably 29% or less. Gd 3+ The content is preferably 8% or less, more preferably 6% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 3+ The content can be 0% or more. From the viewpoint of further reducing the cost and specific gravity of the optical element, Gd 3+ The content is 0%, i.e. Gd 3+ It is particularly preferred that it does not include. Y 3+ From the viewpoint of improving meltability and glass stability, the content is preferably 0% or more, more preferably 1% or more, even more preferably 2% or more, still more preferably 4% or more, even more preferably 6% or more, even more preferably 7% or more, even more preferably 8% or more, and still more preferably 9% or more. 3+The content is preferably 30% or less, more preferably 25% or less, even more preferably 20% or less, even more preferably 17% or less, even more preferably 15% or less, even more preferably 14% or less, even more preferably 13% or less, even more preferably 12% or less, and even more preferably 11% or less.
[0021] Among the rare earth elements, Yb has a large atomic weight and tends to increase the specific gravity of glass. In addition, Yb has absorption in the near infrared region. On the other hand, interchangeable lenses for single-lens reflex cameras and surveillance camera lenses are desired to have high light transmittance in the near infrared region. Therefore, in order to make glass useful for making these lenses, it is necessary to add Yb 3+ From the above viewpoints, it is desirable to have a small content of Yb 3+ The content is preferably 10% or less, more preferably 5% or less, even more preferably 3% or less, and even more preferably 1% or less. 3+ The content can be 0% or more, and Yb 3+ The content is 0%, i.e., Yb 3+ It is particularly preferred that it does not include.
[0022] Ti 4+ , Nb 5+ , W 6+ and Bi 3+ Ti is a component that acts to increase the refractive index, and when contained in an appropriate amount, it also acts to increase the stability of the glass. 4+ , Nb 5+ , W 6+ and Bi 3+ The total content of Ti 4+ +Nb 5+ +W 6+ +Bi 3+From the viewpoint of enhancing the glass stability, Ti is preferably 0% or more, more preferably 5% or more, even more preferably 10% or more, even more preferably 15% or more, even more preferably 16% or more, even more preferably 17% or more, even more preferably 18% or more, even more preferably 19% or more, even more preferably 20% or more, and even more preferably 21% or more. 4+ , Nb 5+ , W 6+ and Bi 3+ The total content of Ti 4+ +Nb 5+ +W 6+ +Bi 3+ ) is preferably 50% or less, more preferably 40% or less, even more preferably 30% or less, still more preferably 29% or less, even more preferably 28% or less, still more preferably 27% or less, even more preferably 26% or less, still more preferably 25% or less, and still more preferably 24% or less, from the viewpoint of maintaining glass stability and suppressing a decrease in the Abbe number.
[0023] From the viewpoint of suppressing high dispersion while maintaining glass stability and from the viewpoint of reducing coloring, the optical glass contains Ti 4+ , Nb 5+ , W 6+ and Bi 3+ La relative to the total content 3+ , Gd 3+ and Y 3+ The cation ratio of the total content of (La 3+ +Gd 3+ +Y 3+ ) / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+)) is 0.30 or more, more preferably 0.40 or more, even more preferably 0.50 or more, even more preferably 0.60 or more, even more preferably 0.70 or more, even more preferably 0.80 or more, even more preferably 0.90 or more, even more preferably 1.00 or more, even more preferably 1.10 or more, even more preferably 1.20 or more, even more preferably 1.30 or more, particularly preferably 1.40 or more, and particularly preferably 1.50 or more. On the other hand, from the viewpoint of maintaining glass stability while suppressing a decrease in refractive index and from the viewpoint of lowering the specific gravity, in the above optical glass, the cation ratio ((La 3+ +Gd 3+ +Y 3+ ) / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ )) is 33.00 or less, preferably 20.00 or less, more preferably 10.00 or less, even more preferably 5.00 or less, even more preferably 4.00 or less, even more preferably 3.00 or less, even more preferably 2.50 or less, even more preferably 2.20 or less, even more preferably 2.00 or less, even more preferably 1.90 or less, even more preferably 1.80 or less, and especially preferably 1.70 or less.
[0024] From the viewpoint of increasing the refractive index, the above optical glass contains Ti 4+ , Nb 5+ , W 6+ and Bi 3+ The total content of Si, a glass network forming component, 4+ and B 3+ The cation ratio of the total content of (Si 4+ +B 3+ ) / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+)) is 34.00 or less, preferably 30.00 or less, more preferably 20.00 or less, even more preferably 10.00 or less, even more preferably 5.00 or less, even more preferably 4.00 or less, even more preferably 3.00 or less, even more preferably 2.50 or less, even more preferably 2.20 or less, even more preferably 2.00 or less, even more preferably 1.90 or less, even more preferably 1.80 or less, particularly preferably 1.70 or less, and particularly preferably 1.60 or less. On the other hand, from the viewpoints of suppressing high dispersion, maintaining glass stability, and reducing coloration, the cation ratio ((Si 4+ +B 3+ ) / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ )) is 0.30 or more, preferably 0.40 or more, more preferably 0.50 or more, even more preferably 0.60 or more, even more preferably 0.70 or more, even more preferably 0.80 or more, even more preferably 0.85 or more, even more preferably 0.90 or more, even more preferably 0.95 or more, even more preferably 1.00 or more, even more preferably 1.05 or more, particularly preferably 1.10 or more, especially preferably 1.15 or more, especially preferably 1.20 or more, especially more preferably 1.25 or more, and especially more preferably 1.30 or more.
[0025] In order to maintain the glass stability and reduce coloration, the above optical glass contains Ti. 4+ , Nb 5+ , W 6+ and Bi 3+ Ti content relative to the total content 4+ Cation ratio of content (Ti 4+ / (Ti 4+ +Nb 5+ +W 6+ +Bi3+ The cation ratio (Ti 4+ / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ )) is preferably 0.70 or more, more preferably 0.75 or more, even more preferably 0.80 or more, even more preferably 0.85 or more, even more preferably 0.90 or more, even more preferably 0.95 or more, and even more preferably 1.00.
[0026] Ti 4+ , Nb 5+ and W 6+ Regarding the content of each component, the preferred ranges are as follows: Ti 4+ The content is preferably 0% or more, more preferably 5% or more, even more preferably 10% or more, even more preferably 15% or more, even more preferably 16% or more, even more preferably 17% or more, even more preferably 18% or more, even more preferably 19% or more, even more preferably 20% or more, and even more preferably 21% or more. 4+ The content is preferably 50% or less, more preferably 40% or less, even more preferably 30% or less, even more preferably 29% or less, even more preferably 28% or less, even more preferably 27% or less, even more preferably 26% or less, even more preferably 25% or less, and even more preferably 24% or less. Nb 5+ The content is preferably 8% or less, more preferably 6% or less, even more preferably 5% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 5+The content can be 0% or more, and from the viewpoint of further reducing the cost of the optical element, Nb 5+ The content is 0%, i.e. Nb 5+ It is particularly preferred that it does not include. W 6+ The content is preferably 8% or less, more preferably 6% or less, even more preferably 5% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 6+ The content can be 0% or more. From the viewpoint of further reducing the cost of optical elements, lowering the specific gravity of the glass, and reducing coloring, W is 6+ The content is 0%, i.e. W 6+ It is particularly preferred that it does not include.
[0027] Nb 5+ and W 6+ and total content (Nb 5+ +W 6+ From the viewpoint of reducing the cost of optical elements and reducing the specific gravity of glass, the total content (Nb 5+ +W 6+ ) can be 0% or more, and is particularly preferably 0%.
[0028] Gd 3+ , Nb 5+ and W 6+ The total content of Gd 3+ +Nb 5+ +W 6+From the viewpoint of reducing the cost of optical elements and reducing the specific gravity of glass, the total content (Gd 3+ +Nb 5+ +W 6+ ) can be 0% or more, and is particularly preferably 0%.
[0029] Bi 3+ Bi is a component that increases the refractive index and decreases the Abbe number. It is also a component that tends to increase the specific gravity and coloring. In order to produce glass that has the above optical properties and is less colored and has a low specific gravity, Bi is an important component. 3+ The preferred ranges of the contents are as follows: Bi 3+ The content is preferably 20% or less, more preferably 15% or less, even more preferably 10% or less, even more preferably 7% or less, even more preferably 5% or less, even more preferably 3% or less, and even more preferably 1% or less. 3+ The content can be 0% or more, and may be 0%.
[0030] Mg 2+ , Ca 2+ , Sr 2+ and Ba 2+ Total content (Mg 2+ +Ca 2+ +Sr 2+ +Ba 2+From the viewpoint of maintaining glass stability and achieving a high refractive index and low dispersion, the total content (Mg) is preferably 20% or less, more preferably 15% or less, even more preferably 10% or less, even more preferably 7% or less, even more preferably 6% or less, even more preferably 5% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 2+ +Ca 2+ +Sr 2+ +Ba 2+ ) can be 0% or more. In one embodiment, the total content (Mg 2+ +Ca 2+ +Sr 2+ +Ba 2+ ) is preferably 0%.
[0031] Mg 2+ , Ca 2+ , Sr 2+ , B.A. 2+ and Zn 2+ Total content (Mg 2+ +Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ From the viewpoints of improving the meltability of the glass, maintaining the glass stability, and suppressing an excessive increase in the glass transition temperature, the total content (Mg 2+ +Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) is preferably 30% or less, more preferably 25% or less, even more preferably 20% or less, even more preferably 15% or less, even more preferably 10% or less, even more preferably 8% or less, even more preferably 6% or less, and even more preferably 4% or less.
[0032] From the viewpoints of maintaining glass stability, increasing the refractive index, and decreasing dispersion, the above optical glass contains La 3+ and Y 3+ and Mg content 2+ , Ca 2+ , Sr 2+ , B.A. 2+ and Zn 2+ The cation ratio of the total content ((Mg 2+ +Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) / (La 3+ +Y 3+ )) is 1.500 or less, preferably 1.000 or less, more preferably 0.800 or less, even more preferably 0.500 or less, even more preferably 0.400 or less, even more preferably 0.300 or less, even more preferably 0.250 or less, even more preferably 0.200 or less, even more preferably 0.150 or less, even more preferably 0.100 or less, even more preferably 0.080 or less, even more preferably 0.060 or less, particularly preferably 0.040 or less, especially preferably 0.020 or less, especially preferably 0.010 or less, especially more preferably 0.007 or less, especially more preferably 0.005 or less. Also, the above cation ratio ((Mg 2+ +Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) / (La 3+ +Y 3+ )) is 0.00 or more, and from the viewpoints of improving the meltability of the glass, maintaining the glass stability, and suppressing an excessive increase in the glass transition temperature, it is preferably 0.00 or more, more preferably 0.001 or more, even more preferably 0.003 or more, and still more preferably 0.005 or more.
[0033] From the viewpoint of maintaining the glass stability and reducing the specific gravity, the above optical glass contains Si 4+ and B 3+ and Mg content 2+ , Ca 2+ , Sr 2+ , B.A. 2+ and Zn 2+ The cation ratio ((Mg 2+ +Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) / (Si 4+ +B 3+ )) is 1.000 or less, preferably 0.900 or less, more preferably 0.800 or less, even more preferably 0.700 or less, even more preferably 0.600 or less, even more preferably 0.550 or less, even more preferably 0.500 or less, even more preferably 0.450 or less, even more preferably 0.400 or less, even more preferably 0.350 or less, even more preferably 0.300 or less, even more preferably 0.250 or less, particularly preferably 0.200 or less, especially preferably 0.150 or less, especially preferably 0.100 or less, especially more preferably 0.090 or less. Also, the cation ratio ((Mg 2+ +Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) / (Si 4+ +B 3+ )) is 0.00 or more, and from the viewpoint of improving the meltability of the glass and suppressing an excessive increase in the glass transition temperature, it is preferably 0.001 or more, more preferably 0.003 or more, and even more preferably 0.005 or more.
[0034] Mg 2+ , Ca 2+ , Sr 2+ and Ba 2+are all components that have the function of improving the meltability of glass. However, if the contents of these components are high, the glass stability tends to decrease. From the above viewpoints, the preferred ranges of the contents of each of these components are as follows. Mg 2+ The content is preferably 20% or less, more preferably 15% or less, even more preferably 10% or less, even more preferably 7% or less, even more preferably 6% or less, even more preferably 5% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 2+ The content can be 0% or more, and may be 0%. Ca 2+ The content is preferably 20% or less, more preferably 15% or less, even more preferably 10% or less, even more preferably 7% or less, even more preferably 6% or less, even more preferably 5% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 2+ The content can be 0% or more, and may be 0%. Sr 2+ The content is preferably 20% or less, more preferably 15% or less, even more preferably 10% or less, even more preferably 7% or less, even more preferably 6% or less, even more preferably 5% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 2+ The content can be 0% or more, and may be 0%. Ba 2+The content is preferably 20% or less, more preferably 15% or less, even more preferably 10% or less, even more preferably 7% or less, even more preferably 6% or less, even more preferably 5% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 2+ The content can be 0% or more, and may be 0%.
[0035] From the viewpoint of improving the meltability, stability, formability, machinability, etc. of glass and realizing the above-mentioned optical properties, Zn 2+ The preferred ranges of the contents are as follows: Zinc 2+ The content can be 0% or more, preferably 0.03% or more, more preferably 0.05% or more, even more preferably 0.08% or more, and even more preferably 0.1% or more. Zn 2+ The content is preferably 30% or less, more preferably 25% or less, even more preferably 20% or less, even more preferably 15% or less, even more preferably 10% or less, even more preferably 8% or less, even more preferably 6% or less, and even more preferably 4% or less.
[0036] Zinc 2+ Regarding La, from the viewpoint of improving the glass stability while realizing the above-mentioned optical properties, 3+ and Y 3+ Zn content relative to the total content of 2+ Cation ratio of content (Zn 2+ / (La 3+ +Y 3)) is preferably 0.66 or less, more preferably 0.50 or less, even more preferably 0.40 or less, even more preferably 0.30 or less, even more preferably 0.25 or less, even more preferably 0.20 or less, even more preferably 0.15 or less, even more preferably 0.13 or less, even more preferably 0.12 or less, even more preferably 0.11 or less, even more preferably 0.10 or less, particularly preferably 0.090 or less, particularly preferably 0.085 or less, and particularly preferably 0.080 or less. Also, the cation ratio (Zn 2+ / (La 3+ +Y 3+ A small cation ratio (Zn) is also preferable from the viewpoints of suppressing the decrease in glass transition temperature (thereby improving machinability) and improving chemical durability. 2+ / (La 3+ +Y 3+ The cation ratio (Zn) can be 0.00% or more, and is preferably more than 0.00% from the viewpoints of improving meltability and suppressing an excessive increase in the glass transition temperature. 2+ / (La 3+ +Y 3+ )) is more preferably 0.001 or more, even more preferably 0.003 or more, and even more preferably 0.005 or more.
[0037] La 3+ Zn content 2+ and Ba 2+ The cation ratio of the total content of Zn 2+ +Ba 2+ ) / La 3+ From the viewpoint of improving the glass stability while realizing the above-mentioned optical properties, the cation ratio ((Zn 2+ +Ba 2+ ) / La3+ ) is preferably 0.66 or less, more preferably 0.50 or less, even more preferably 0.40 or less, still more preferably 0.30 or less, still more preferably 0.25 or less, still more preferably 0.20 or less, still more preferably 0.16 or less, still more preferably 0.14 or less, still more preferably 0.13 or less, still more preferably 0.12 or less, still more preferably 0.11 or less, particularly preferably 0.100 or less, and particularly more preferably 0.090 or less.
[0038] La 3+ and Y 3+ Zn content relative to the total content of 2+ and Ba 2+ The cation ratio of the total content of Zn 2+ +Ba 2+ ) / (La 3+ +Y 3+ From the viewpoint of improving the glass stability while realizing the above-mentioned optical properties, the cation ratio ((Zn 2+ +Ba 2+ ) / (La 3+ +Y 3+)) is preferably 0.66 or less, more preferably 0.50 or less, even more preferably 0.40 or less, even more preferably 0.30 or less, even more preferably 0.25 or less, even more preferably 0.20 or less, even more preferably 0.15 or less, even more preferably 0.13 or less, even more preferably 0.12 or less, even more preferably 0.11 or less, even more preferably 0.10 or less, particularly preferably 0.090 or less, particularly preferably 0.085 or less, and especially preferably 0.080 or less.
[0039] Li + Li has a strong effect of lowering the glass transition temperature, so as its content increases, machinability tends to decrease. In addition, glass stability, chemical durability, and weather resistance also tend to decrease. + The content is preferably 10% or less, more preferably 8% or less, even more preferably 6% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. + The content can be 0% or more, and may be 0%.
[0040] Na + , K + , Rb + and Cs + All of these elements have the function of improving the melting properties of glass, but when their contents increase, glass stability, chemical durability, weather resistance, and machinability tend to decrease. + , K + , Rb + and Cs + The preferred ranges of the contents of each of the above are as follows: Na +The content is preferably 10% or less, more preferably 8% or less, even more preferably 6% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. + The content can be 0% or more, and may be 0%. K + The content is preferably 10% or less, more preferably 8% or less, even more preferably 6% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. + The content can be 0% or more, and may be 0%. Rb + The content is preferably 10% or less, more preferably 8% or less, even more preferably 6% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. + The content can be 0% or more, and may be 0%. Cs + The content is preferably 10% or less, more preferably 8% or less, even more preferably 6% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. + The content can be 0% or more, and may be 0%.
[0041] Al 3+ is a component that improves the chemical durability and weather resistance of glass. 3+ When the content of Al is high, there may be a tendency for the refractive index, glass stability, and melting property to decrease. 3+ The preferred ranges of the contents are as follows: Al 3+ The content is preferably 10% or less, more preferably 8% or less, even more preferably 6% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 3+ The content can be 0% or more, and may be 0%.
[0042] Zr 4+ Zr is a component that acts to increase the refractive index, and when contained in an appropriate amount, it also acts to improve glass stability. 4+ Zr also has the effect of increasing the glass transition temperature, thereby making the glass less susceptible to breakage during mechanical processing. From the viewpoint of obtaining these effects effectively, Zr 4+ The content is preferably 0% or more, more preferably 1% or more, even more preferably 2% or more, even more preferably 3% or more, and even more preferably 4% or more. From the viewpoint of improving glass stability, Zr 4+ It is preferred that the content is 15% or less, more preferably 13% or less, even more preferably 10% or less, even more preferably 9% or less, even more preferably 8% or less, even more preferably 7% or less, and even more preferably 6% or less.
[0043] P 5+ is a component that lowers the refractive index and also reduces glass stability, but when introduced in a very small amount, it can improve glass stability. In order to obtain a glass having the above optical properties and excellent glass stability, P 5+ The preferred ranges of the contents are as follows: P 5+ The content is preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 5+ The content can be 0% or more, and may be 0%.
[0044] Ga 3+ , In 3+ , Sc 3+ and Hf 4+ All of these components have the function of increasing the refractive index. However, these components are not essential components for obtaining the above glass. 3+ , In 3+ , Sc 3+ and Hf 4+ The preferred ranges of the contents of each of the above are as follows: Ga 3+ The content is preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, still more preferably 2% or less, and even more preferably 1% or less. 3+ The content can be 0% or more, and may be 0%. In 3+ The content is preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 3+ The content can be 0% or more, and may be 0%. Sc 3+ The content is preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 3+ The content can be 0% or more, and may be 0%. Sc 3+ The content is preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 3+ The content can be 0% or more, and may be 0%. Hf 4+The content is preferably 10% or less, more preferably 8% or less, even more preferably 6% or less, even more preferably 4% or less, and even more preferably 2% or less. 4+ The content can be 0% or more, and may be 0%.
[0045] Lu 3+ Lu has the function of increasing the refractive index, but it also increases the specific gravity of the glass. In addition, Lu is a heavy rare earth element like Gd and Yb, so from the perspective of a stable supply of glass, Lu 3+ From the above viewpoints, it is desirable for the content of Lu to be low. 3+ The content is preferably 10% or less, more preferably 8% or less, even more preferably 6% or less, still more preferably 4% or less, and even more preferably 2% or less. 3+ The content can be 0% or more, and may be 0%.
[0046] Ge 4+ Although it has the function of increasing the refractive index, from the viewpoint of further reducing the cost of optical elements, Ge 4+ The content is preferably 10% or less, more preferably 8% or less, even more preferably 6% or less, even more preferably 4% or less, and even more preferably 2% or less. 4+ The content can be 0% or more, and may be 0%.
[0047] Te 4+ Te is a component that increases the refractive index, but from the perspective of environmental considerations, 4+ The content is preferably small. 4+ The content is preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and even more preferably 1% or less. 4+ The content can be 0% or more, and may be 0%.
[0048] Pb, As, Cd, Tl, Be and Se are each toxic, and therefore it is preferable not to contain these elements, i.e., not to introduce these elements into the glass as glass components. U, Th and Ra are all radioactive elements, and therefore it is preferable not to contain these elements, i.e., not to introduce these elements into the glass as glass components. V, Cr, Mn, Fe, Co, Ni, Cu, Pr, Nd, Pm, Sm, Eu, Tb, Dy, Ho, Er, Tm and Ce are undesirable elements to be contained in glass for optical elements because they increase the coloring of the glass and are sources of fluorescence. Therefore, it is preferable not to contain these elements, i.e., not to introduce these elements into the glass as glass components.
[0049] Sb and Sn are optional elements that function as fining agents. The Sb content of the above optical glass is Sb 3+ The content of Sb can be, for example, 0.40% or less, 0.20% or less, 0.10% or less, 0.05% or less, 0.02% or less, or 0.01% or less. 3+ The content can be 0.00% or more, and can also be 0.00%. The Sn content of the above optical glass is Sn 2+ The content of Sb can be, for example, 0.40% or less, 0.20% or less, 0.10% or less, 0.05% or less, 0.02% or less, or 0.01% or less. 3+ The content can be 0.00% or more, and can also be 0.00%.
[0050] Now that the cationic component has been described, the anionic component will be described.
[0051] The optical glass may be an oxide glass, and may contain O as an anion component. 2- It can include 2-The content is preferably 95.0 anion % or more, more preferably 97.0 anion % or more, even more preferably 98.0 anion % or more, still more preferably 99.0 anion % or more, even more preferably 99.5 anion % or more, and may be 100 anion %.
[0052] O 2- The other anion components are F - , Cl - , Br - and I - Here, F - , Cl - , Br - and I - Both of these components are prone to volatilization during glass melting. The volatilization of these components tends to cause the physical properties of the glass to change, reducing the homogeneity of the glass and causing considerable wear on the melting equipment. - , Cl - , Br - and I - The total content of O 2- It is preferable to reduce the content of
[0053] <Glass properties> (Refractive index nd, Abbe number νd) The above optical glass is a high-refractive-index, low-dispersion glass having a refractive index nd in the range of 1.9000 to 2.1500 and an Abbe number vd in the range of 20.0 to 35.0. From the viewpoint of usefulness as a material for optical elements, the preferred ranges of the refractive index nd and the Abbe number vd are as follows: The refractive index nd is 1.9000 or more, preferably 1.9500 or more, more preferably 1.9600 or more, even more preferably 1.9700 or more, even more preferably 1.9800 or more, even more preferably 1.9850 or more, even more preferably 1.9900 or more, even more preferably 1.9950 or more, and even more preferably 2.0000 or more. The refractive index nd is 2.1500 or less, preferably 2.1000 or less, more preferably 2.0500 or less, even more preferably 2.0300 or less, even more preferably 2.0100 or less, and even more preferably 2.0020 or less. The Abbe number νd is a value that represents the properties related to dispersion, and is expressed as νd=(nd-1) / (nF-nC) using the refractive indices nd, nF, and nC at the d-line, F-line, and C-line. The Abbe number is 35.0 or less, preferably 34.0 or less, more preferably 33.0 or less, even more preferably 32.0 or less, even more preferably 31.0 or less, even more preferably 30.5 or less, even more preferably 30.0 or less, and even more preferably 29.5 or less. The Abbe number νd is 20.0 or more, preferably 21.0 or more, more preferably 22.0 or more, even more preferably 23.0 or more, even more preferably 24.0 or more, even more preferably 25.0 or more, even more preferably 26.0 or more, even more preferably 27.0 or more, even more preferably 27.5 or more, even more preferably 28.0 or more, and even more preferably 28.3 or more. It is also preferable that the refractive index nd and the Abbe number vd satisfy one or more of the following relations. nd≧2.3700-0.0140×νd nd ≥ 2.1450-0.0070 × νd nd≧2.3900-0.0140×νd nd≧2.1510-0.0070×νd nd≧2.3960-0.0140×νd nd≧2.1550-0.0070×νd nd≧2.4000-0.0140×νd nd≧2.1600-0.0070×νd nd≧2.1700-0.0070×νd nd≧2.0715-0.0380×νd nd≧2.0915-0.0380×νd nd≧2.1015-0.0380×νd nd≦2.4900-0.0140×νd nd≦2.4500-0.0140×νd nd≦2.4300-0.0140×νd nd≦2.4200-0.0140×νd In the present invention and this specification, unless otherwise specified, "refractive index" means "refractive index nd" and "Abbe number" means "Abbe number vd".
[0054] (Partial dispersion characteristic Pg,F) From the viewpoint of correcting chromatic aberration, the optical glass is preferably one having a small partial dispersion ratio when the Abbe number vd is fixed. Here, the partial dispersion ratio Pg,F is expressed as (ng-nF) / (nF-nc) using the refractive indices ng, nF, and nc for the g-line, F-line, and c-line, respectively. From the viewpoint of providing a high refractive index, low dispersion glass suitable for correcting high-order chromatic aberrations, the preferred range of the partial dispersion ratio Pg,F of the above optical glass is as follows. The partial dispersion ratio Pg,F is preferably 0.6500 or less, more preferably 0.6300 or less, even more preferably 0.6200 or less, even more preferably 0.6100 or less, and even more preferably 0.6000 or less. The partial dispersion ratio Pg,F is preferably 0.5700 or more, more preferably 0.5800 or more, even more preferably 0.5820 or more, even more preferably 0.5850 or more, and even more preferably 0.590 or more.
[0055] (Liquidus temperature LT) From the viewpoint of suppressing crystallization during glass production, the liquidus temperature LT of the optical glass is preferably 1400°C or less, more preferably 1380°C or less, even more preferably 1360°C or less, even more preferably 1340°C or less, even more preferably 1320°C or less, even more preferably 1310°C or less, even more preferably 1300°C or less, even more preferably 1290°C or less, even more preferably 1280°C or less, even more preferably 1270°C or less, and even more preferably 1260°C or less. The liquidus temperature LT can be, for example, 1150°C or more. However, since a low liquidus temperature is preferable, the liquidus temperature may be lower than 1150°C, and the lower limit is not particularly limited.
[0056] (glass transition temperature Tg) The glass transition temperature Tg of the optical glass is not particularly limited, but is preferably 630°C or higher from the viewpoint of machinability. By setting the glass transition temperature at 630°C or higher, the glass can be made less likely to break during mechanical processing of the glass, such as cutting, milling, grinding, and polishing. From the viewpoint of machinability, the glass transition temperature Tg is more preferably 640°C or higher, even more preferably 700°C or higher, even more preferably 710°C or higher, even more preferably 720°C or lower, even more preferably 730°C or higher, even more preferably 740°C or higher, and even more preferably 745°C or higher. On the other hand, from the viewpoint of reducing the load on the annealing furnace and the molding die, the glass transition temperature Tg is preferably 800°C or lower, more preferably 790°C or lower, even more preferably 780°C or lower, even more preferably 775°C or lower, even more preferably 770°C or lower, even more preferably 765°C or lower, and even more preferably 760°C or lower.
[0057] (specific gravity, specific gravity / nd) The refractive power of the optical elements (lenses) that make up an optical system is determined by the refractive index of the glass that makes up the lens and the curvature of the lens's optically functional surface (the surface through which the light rays to be controlled enter and exit). If you try to increase the curvature of the optically functional surface, the thickness of the lens also increases. As a result, the lens becomes heavier. In contrast, if glass with a high refractive index is used, it is possible to obtain a large refractive power without increasing the curvature of the optically functional surface. From the above, if the refractive index can be increased while suppressing an increase in the specific gravity of the glass, it will be possible to reduce the weight of an optical element having a certain refractive power. From the above viewpoints, the specific gravity of the optical glass is preferably 5.40 or less, more preferably 5.35 or less, even more preferably 5.30 or less, even more preferably 5.25 or less, even more preferably 5.20 or less, even more preferably 5.15 or less, even more preferably 5.10 or less, even more preferably 5.05 or less, and even more preferably 5.00 or less. Since the lower the specific gravity, the more preferable it is from the viewpoint of reducing the weight of the optical element, the lower limit of the specific gravity of the optical glass is not particularly limited. In one embodiment, the specific gravity of the optical glass can be, for example, 4.30 or more, 4.40 or more, 4.50 or more, 4.60 or more, 4.70 or more, 4.75 or more, 4.77 or more, 4.80 or more, or 4.85 or more. From the same viewpoint, the value (specific gravity / nd) obtained by dividing the specific gravity of the optical glass by the refractive index nd is preferably 2.80 or less, more preferably 2.70 or less, even more preferably 2.65 or less, even more preferably 2.60 or less, even more preferably 2.56 or less, even more preferably 2.54 or less, even more preferably 2.52 or less, even more preferably 2.51 or less, and even more preferably 2.50 or less. Since the smaller the value of "specific gravity / nd" is, the more preferable it is from the viewpoint of reducing the weight of the optical element, the lower limit of the value of "specific gravity / nd" of the optical glass is not particularly limited. In one embodiment, the "specific gravity / nd" of the optical glass can be, for example, 2.20 or more, 2.30 or more, 2.35 or more, 2.36 or more, 2.37 or more, 2.38 or more, 2.39 or more, 2.40 or more, 2.41 or more, 2.42 or more, or 2.43 or more.
[0058] (Coloring degree λ5, λ70) The light transmittance of glass, specifically, the suppression of the shift to longer wavelengths of the light absorption edge on the short wavelength side, can be evaluated by the coloring degree λ5. The coloring degree λ5 represents the wavelength at which the spectral transmittance (including surface reflection loss) of a glass with a thickness of 10 mm is 5% from the ultraviolet region to the visible region. The λ5 shown in the examples described later is a value measured in a wavelength region of 250 to 700 nm. More specifically, the spectral transmittance is, for example, the spectral transmittance obtained by using a glass sample having parallel flat surfaces polished to a thickness of 10.0±0.1 mm and irradiating light perpendicularly to the polished surfaces, that is, Iout / Iin, where Iin is the intensity of light incident on the glass sample and Iout is the intensity of light transmitted through the glass sample. According to the coloring degree λ5, the absorption edge on the short wavelength side of the spectral transmittance can be quantitatively evaluated. When lenses are bonded together with an ultraviolet-curable adhesive to produce a cemented lens, the adhesive is irradiated with ultraviolet light through an optical element to cure the adhesive. From the viewpoint of efficiently curing the ultraviolet-curable adhesive, it is preferable that the absorption edge on the short wavelength side of the spectral transmittance is in a short wavelength range. The coloring degree λ5 can be used as an index for quantitatively evaluating the absorption edge on the short wavelength side. The optical glass can exhibit a λ5 of preferably 400 nm or less, more preferably 390 nm or less, even more preferably 385 nm or less, even more preferably 380 nm or less, even more preferably 378 nm or less, even more preferably 376 nm or less, even more preferably 374 nm or less, even more preferably 372 nm or less, and even more preferably 370 nm or less. The lower the λ5, the more preferable, and the lower limit is not particularly limited. In one embodiment, the λ5 of the optical glass can be 330 nm or more, 340 nm or more, 345 nm or more, 350 nm or more, 355 nm or more, 356 nm or more, 357 nm or more, 358 nm or more, 359 nm or more, 360 nm or more, 361 nm or more, 362 nm or more, or 363 nm or more.
[0059] On the other hand, the coloring degree λ70 can also be mentioned as an index of the coloring degree of glass. λ70 represents the wavelength at which the spectral transmittance measured by the method described for λ5 is 70%. From the viewpoint of obtaining glass with little coloring, λ70 is preferably 500 nm or less, more preferably 490 nm or less, even more preferably 480 nm or less, even more preferably 470 nm or less, even more preferably 460 nm or less, even more preferably 457 nm or less, even more preferably 455 nm or less, even more preferably 450 nm or less, even more preferably 445 nm or less, and even more preferably 440 nm or less. The lower the λ70, the more preferable it is, and the lower limit is not particularly limited. In one embodiment, the λ70 of the optical glass can be 370 nm or more, 380 nm or more, 390 nm or more, 400 nm or more, 410 nm or more, 420 nm or more, 425 nm or more, 430 nm or more, or 435 nm or more.
[0060] (λ5 / nd, λ5 / νd, λ70 / nd, λ70 / νd) Regarding the degree of coloration, it is preferable that the refractive index can be increased while suppressing an increase in the degree of coloration of the glass. It is also preferable that the dispersion can be reduced while suppressing an increase in the degree of coloration of the glass. From the above viewpoints, the value (λ5 / nd) obtained by dividing λ5 by the refractive index nd of the optical glass is preferably 195.00 nm or less, more preferably 190.00 nm or less, even more preferably 188.00 nm or less, even more preferably 187.00 nm or less, even more preferably 187.50 nm or less, even more preferably 187.00 nm or less, even more preferably 186.50 nm or less, even more preferably 186.00 nm or less, even more preferably 185.55 nm or less, and even more preferably 185.00 nm or less. Also, the lower λ5 / nd is the more preferable, and there is no particular lower limit. In one embodiment, the λ5 / nd of the optical glass can be 160.00 nm or more, 170.00 nm or more, 171.00 nm or more, 172.00 nm or more, 173.00 nm or more, 174.00 nm or more, 175.00 nm or more, 176.00 nm or more, 177.00 nm or more, or 178.00 nm or more. The value (λ5 / νd) obtained by dividing λ5 of the optical glass by the Abbe number νd is preferably 20.00 nm or less, more preferably 15.00 nm or less, even more preferably 14.00 nm or less, even more preferably 13.00 nm or less, even more preferably 12.90 nm or less, even more preferably 12.80 nm or less, and even more preferably 12.70 nm or less. The lower λ5 / νd is the better, and there is no particular lower limit. In one embodiment, the λ5 / νd of the optical glass can be 8.00 nm or more, 8.50 nm or more, 9.00 nm or more, 9.50 nm or more, 10.00 nm or more, 10.50 nm or more, 11.00 nm or more, 11.50 nm or more, 11.70 nm or more, 12.00 nm or more, 12.10 nm or more, 12.20 nm or more, 12.30 nm or more, 12.40 nm or more, or 12.50 nm or more. The value (λ70 / nd) obtained by dividing λ70 of the optical glass by the refractive index nd is preferably 270.00 nm or less, more preferably 260.00 nm or less, even more preferably 250.00 nm or less, even more preferably 240.00 nm or less, even more preferably 235.00 nm or less, even more preferably 230.00 nm or less, even more preferably 227.00 nm or less, and even more preferably 225.00 nm or less. The lower λ70 / nd is more preferable, and the lower limit is not particularly limited. In one embodiment, the λ70 / nd of the optical glass can be 190.00 nm or more, 200.00 nm or more, 205.00 nm or more, 210.00 nm or more, 212.00 nm or more, 214.00 nm or more, 216.00 nm or more, 218.00 nm or more, or 220.00 nm or more. The value (λ70 / νd) obtained by dividing λ70 of the optical glass by the Abbe number νd is preferably 25.00 nm or less, more preferably 22.00 nm or less, even more preferably 20.00 nm or less, even more preferably 19.00 nm or less, even more preferably 18.00 nm or less, even more preferably 17.00 nm or less, and even more preferably 16.00 nm or less. The lower λ70 / νd is more preferable, and the lower limit is not particularly limited. In one embodiment, the λ70 / νd of the optical glass can be 8.00 nm or more, 9.00 nm or more, 10.00 nm or more, 11.00 nm or more, 12.00 nm or more, 13.00 nm or more, 14.00 nm or more, or 15.00 nm or more.
[0061] <Glass manufacturing method> The optical glass can be obtained, for example, by blending, melting, and molding glass raw materials so as to obtain the required characteristics. As the glass raw materials, for example, phosphates, fluorides, alkali metal compounds, alkaline earth metal compounds, etc. may be used. The glass may be melted and molded by known methods.
[0062] [Glass material for press molding, optical element blanks, and their manufacturing methods] Another aspect of the present invention is a glass material for press molding comprising the optical glass; an optical element blank made of the optical glass; Regarding.
[0063] According to another aspect of the present invention, a method for producing a glass material for press molding, comprising a step of molding the optical glass into a glass material for press molding; a method for producing an optical element blank, comprising a step of press-molding the above-mentioned glass material for press molding using a press mold to produce an optical element blank; A method for producing an optical element blank, comprising the step of forming the optical glass into an optical element blank; will also be provided.
[0064] An optical element blank is an optical element base material that approximates the shape of a target optical element and has polishing margins (surface layers to be removed by polishing) and, if necessary, grinding margins (surface layers to be removed by grinding) added to the shape of the optical element. The optical element is finished by grinding and polishing the surface of the optical element blank. In one embodiment, the optical element blank can be produced by a method (called a direct press method) in which a molten glass obtained by melting an appropriate amount of the optical glass is press-molded. In another embodiment, the optical element blank can also be produced by solidifying a molten glass obtained by melting an appropriate amount of the glass.
[0065] In another embodiment, a glass material for press molding is prepared, and the prepared glass material for press molding is press molded to produce an optical element blank.
[0066] The press molding of the glass material for press molding can be carried out by a known method in which the glass material for press molding in a heated and softened state is pressed in a press mold. Both heating and press molding can be carried out in the atmosphere. By annealing after press molding to reduce distortion inside the glass, a homogeneous optical element blank can be obtained.
[0067] Glass materials for press molding include not only glass gobs for press molding that are directly subjected to press molding for producing optical element blanks, but also glass gobs for press molding that are mechanically processed, such as by cutting, grinding, and polishing, and then subjected to press molding. Cutting methods include a method in which a groove is formed in the portion of the surface of the glass plate to be cut by a method called scribing, and local pressure is applied to the groove portion from the back side of the surface on which the groove is formed, thereby breaking the glass plate at the groove portion, and a method in which the glass plate is cut by a cutting blade. Grinding and polishing methods include barrel polishing.
[0068] The glass material for press molding can be produced, for example, by casting molten glass into a mold to form a glass plate, and cutting this glass plate into a plurality of glass pieces. Alternatively, a suitable amount of molten glass can be molded to produce a glass gob for press molding. An optical element blank can also be produced by reheating, softening, and press-molding the glass gob for press molding. The method of producing an optical element blank by reheating, softening, and press-molding glass is called a reheat press method, as opposed to a direct press method.
[0069] [Optical element and its manufacturing method] Another aspect of the present invention is An optical element made of the above optical glass Regarding. The optical element is produced using the optical glass. In the optical element, the glass surface may be coated with one or more layers of coating, such as a multilayer film including an anti-reflection film.
[0070] According to another aspect of the present invention, A method for producing an optical element, comprising the step of producing an optical element by grinding and / or polishing the optical element blank; will also be provided.
[0071] In the manufacturing method of the optical element, known methods may be used for grinding and polishing, and by thoroughly cleaning and drying the surface of the optical element after processing, an optical element with high internal quality and surface quality can be obtained. In this way, an optical element made of the optical glass can be obtained. Examples of optical elements include various lenses such as spherical lenses, aspherical lenses, and microlenses, and prisms.
[0072] In addition, the optical element made of the optical glass is also suitable as a lens constituting a cemented optical element. Examples of cemented optical elements include a cemented lens formed by cementing lenses together, and a lens and a prism. For example, a cemented optical element can be produced by precisely processing (for example, spherical polishing) the cemented surfaces of two optical elements to be cemented so that the shapes are inverted, applying an ultraviolet-curing adhesive used for bonding the cemented lens, bonding them together, and then irradiating ultraviolet rays through the lens to cure the adhesive. The optical glass is preferable as an optical element material for producing such a cemented optical element. A plurality of optical elements to be cemented are produced using a plurality of types of optical glass having different Abbe numbers νd, and cemented together to produce an element suitable for correcting chromatic aberration.
[0073] As a result of quantitative analysis of glass composition, glass components are sometimes expressed on an oxide basis, and the content of glass components is sometimes expressed in mass%. The composition expressed in mass% on an oxide basis in this way can be converted to a composition expressed in cation% and anion% by, for example, the following method. If the glass contains N kinds of glass components, the kth glass component is A(k). m O n Here, k is an arbitrary integer between 1 and N. A(k) is a cation, O is oxygen, and m and n are stoichiometric integers. For example, in the case of B2O3, m=2 and n=3, and in the case of SiO2, m=1 and n=2. Next, A(k) m O n The content of A(k) is X(k) [mass%]. Here, if the atomic weight of A(k) is P(k) and the atomic number of oxygen O is Q, then A(k) m O n The formal molecular weight R(k) of R(k) = P(k) x m + Q x n It becomes. Furthermore, B = 100 / {Σ[m×X(k) / R(k)]} Then, the cationic component A(k) s+The content (cation %) of is [X(k) / R(k)]×m×B(cation %). Here, Σ means the sum of m×X(k) / R(K) for k=1 to N. m changes depending on k. s is 2n / m. The molecular weight R(k) may be calculated by rounding off the fourth decimal place and displaying the value to the third decimal place. The molecular weights of some glass components and additives expressed on an oxide basis are shown in Table 1 below.
[0074] [Table 1] EXAMPLES
[0075] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the embodiments shown in the examples.
[0076] <Example 1> In order to obtain the glass composition shown in the table below, the corresponding nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc. were used as raw materials for introducing each component, and the raw materials were weighed and thoroughly mixed to obtain blended raw materials. The raw materials were placed in a platinum crucible and heated to melt. After melting, the molten glass was poured into a mold and allowed to cool to near the glass transition temperature. It was then immediately placed in an annealing furnace and annealed for about 1 hour within the glass transition temperature range. After that, it was allowed to cool to room temperature in the furnace, and the optical glasses (oxide glasses) shown in Table 1 were obtained. The anion components of each optical glass shown in the table below are O 2- The content is 100% anion. When the obtained optical glass was observed under magnification with an optical microscope, no crystal precipitation, foreign matter such as platinum particles, bubbles, or striae were observed. The physical properties of the optical glass thus obtained are shown in the following table. The physical properties of the optical glasses were measured by the methods described below.
[0077] <Evaluation of physical properties of optical glass> (1) Refractive index nd, ng, nF, nC and Abbe number νd The glass obtained by cooling at a cooling rate of -30°C / hour was measured for refractive indexes nd, ng, nF, nC and Abbe number vd according to the refractive index measurement method specified by the Japan Optical Glass Industry Association.
[0078] (2) Partial dispersion ratio Pg,F The partial dispersion ratio Pg,F was calculated from the refractive indices ng, nF, and nC obtained in (1) above.
[0079] (3) Glass transition temperature Tg The glass transition temperature Tg was measured using a differential scanning calorimeter (DSC3300) manufactured by NETZSCH at a heating rate of 10° C. / min.
[0080] (4) Liquidus temperature LT Glass samples (volume: 10 cm) made of each glass shown in the table below 3 ) was placed in a platinum crucible and held in a glass melting furnace set at 1400°C for 20 minutes to fully melt the glass sample into a molten state, and then the platinum crucible was removed from the glass melting furnace and the glass sample was left in the platinum crucible until the temperature of the glass sample became 500°C or less to cool. Then, the platinum crucible was placed in a glass melting furnace set at a temperature of T°C and held for 2 hours, and after being removed from the furnace, the platinum crucible containing the glass sample was immediately (within 8 seconds) placed on a refractory material (bricks, etc.) at room temperature to cool the glass sample to room temperature. The room temperature here is a temperature in the range of -10 to 80°C. Then, the surface and inside of the glass sample were visually observed to confirm the presence or absence of crystals. The above experiment was repeated while changing the temperature T°C in increments of 10°C within the range of 1100 to 1350°C, and the lowest temperature at which no crystals were observed on the surface or inside of the glass sample was determined as the liquidus temperature LT.
[0081] (5) Specific gravity, specific gravity / nd Specific gravity was measured by Archimedes' method. The measured specific gravity was divided by the refractive index nd determined in (1) above to calculate the value (specific gravity / nd).
[0082] (6) Coloring degree λ5, λ70 A glass sample having a thickness of 10±0.1 mm and two optically polished flat surfaces facing each other was used, and light with intensity Iin was incident perpendicularly to the polished surfaces using a spectrophotometer. The intensity Iout of the light transmitted through the glass sample was measured, and the spectral transmittance Iout / Iin was calculated. The wavelength at which the spectral transmittance was 5% was defined as λ5, and the wavelength at which the spectral transmittance was 70% was defined as λ70.
[0083] (7)λ5 / nd, λ5 / νd, λ70 / nd, λ70 / νd From the nd, vd, λ5 and λ70 determined above, λ5 / nd, λ5 / vd, λ70 / nd and λ70 / vd were calculated.
[0084] The above results are shown in Table 2 below (Tables 2-1 to 2-6).
[0085] [Table 2-1]
[0086] [Table 2-2]
[0087] [Table 2-3]
[0088] [Table 2-4]
[0089] [Table 2-5]
[0090] [Table 2-6]
[0091] <Evaluation of glass stability> Glass is obtained by molding molten glass. If glass stability is low, the number of crystal grains contained in the glass obtained by pouring molten glass into a mold and molding it increases. Therefore, glass stability, particularly devitrification resistance when molding a molten glass, can be evaluated based on the number of crystals contained in glass melted and molded under certain conditions. An example of the evaluation method is shown below. Nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc. are used as raw materials, and each raw material powder is weighed and thoroughly mixed to prepare a blended raw material. This blended raw material is placed in a 300 ml platinum crucible and heated and melted for 2 hours in a glass melting furnace set at 1400°C to produce 150 g of homogeneous molten glass. During this time, the molten glass is stirred and shaken several times. After two hours have passed, the crucible containing the molten glass is removed from the furnace and stirred and shaken for 15 to 20 seconds. The molten glass is then poured into a carbon mold (50 mm x 40 mm x 8 mm to 12 mm) and placed in an annealing furnace to remove any distortion. The inside of the obtained glass is observed using an optical microscope (magnification 100x), the number of precipitated crystals is counted, and the number of crystals contained per kg of glass is calculated to obtain the number density of the crystals (pieces / kg). The number density of crystals evaluated by the above method is preferably 2000 / kg or less, more preferably 1000 / kg or less, even more preferably 800 / kg or less, even more preferably 600 / kg or less, even more preferably 400 / kg or less, even more preferably 200 / kg or less, even more preferably 100 / kg or less, even more preferably 50 / kg or less, even more preferably 30 / kg or less, and particularly preferably 0 / kg. The number density of crystals of each glass shown in Table 2 evaluated by the above method was all 0 / kg.
[0092] <Example 2> A glass gob for press molding was prepared using the various glasses obtained in Example 1. The glass gob was heated and softened in the atmosphere, and press molded in a press mold to prepare a lens blank (optical element blank). The prepared lens blank was removed from the press mold, annealed, and machined, including polishing, to prepare a spherical lens made of the various glasses prepared in Example 1.
[0093] <Example 3> A desired amount of the molten glass produced in Example 1 was press molded in a press mold to produce a lens blank (optical element blank). The produced lens blank was removed from the press mold, annealed, and subjected to mechanical processing including polishing to produce a spherical lens made of the various glasses produced in Example 1.
[0094] <Example 4> The molten glass produced in Example 1 was solidified to produce a glass lump (optical element blank), which was then annealed and machined, including polishing, to produce spherical lenses made of the various glasses produced in Example 1.
[0095] <Example 5> The spherical lenses produced in Examples 2 to 4 were bonded to spherical lenses made of other types of glass to produce cemented lenses. The cemented surfaces of the spherical lenses produced in Examples 2 to 4 were convex, and the cemented surfaces of the spherical lenses made of other types of optical glass were concave. The above two cemented surfaces were produced so that the absolute values of the radii of curvature were equal to each other. An ultraviolet-curable adhesive for bonding optical elements was applied to the cemented surfaces, and the two lenses were bonded together with their cemented surfaces facing each other. Thereafter, the adhesive applied to the cemented surfaces was irradiated with ultraviolet light through the spherical lenses produced in Examples 2 to 4 to solidify the adhesive. A cemented lens was produced in the manner described above.
[0096] Finally, the above-mentioned aspects will be summarized.
[0097] According to one embodiment, in the glass composition expressed in cation %, Ta 5+ The content is in the range of 0 to 5% cationic Ti4+ , Nb 5+ , W 6+ and Bi 3+ Ti content relative to the total content 4+ Cation ratio of content (Ti 4+ / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ )) is in the range of 0.60 to 1.00, and La 3+ , Gd 3+ and Y 3+ Si content relative to the total content 4+ and B 3+ The cation ratio of the total content of (Si 4+ +B 3+ ) / (La 3+ +Gd 3+ +Y 3+ ) is in the range of 0.30 to 2.40, and Ti 4+ , Nb 5+ , W 6+ and Bi 3+ Si content relative to the total content 4+ and B 3+ The cation ratio of the total content of (Si 4+ +B 3+ ) / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ )) is in the range of 0.30 to 34.00, and Ti 4+ , Nb 5+ , W 6+ and Bi 3+ La relative to the total content 3+ , Gd 3+ and Y 3+ The cation ratio of the total content of (La 3+ +Gd 3+ +Y 3+ ) / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ )) is in the range of 0.30 to 33.00, and La 3+ and Y 3+ and Mg content 2+ , Ca 2+ , Sr 2+ , B.A. 2+and Zn 2+ The cation ratio of the total content ((Mg 2+ +Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) / (La 3+ +Y 3+ )) is in the range of 0.00 to 1.50, and Si 4+ and B 3+ and Mg content 2+ , Ca 2+ , Sr 2+ , B.A. 2+ and Zn 2+ The cation ratio ((Mg 2+ +Ca 2+ +Sr 2+ +Ba 2+ +Zn 2+ ) / (Si 4+ +B 3+ )) is in the range of 0.00 to 1.00, and Si 4+ , B 3+ , Zn 2+ , La 3+ , Y 3+ , Zr 4+ and Ti 4+ Gd content relative to the total 3+ , Nb 5+ and W 6+ The cation ratio of the total content of (Gd 3+ +Nb 5+ +W 6+ ) / (Si 4+ +B 3+ +Zn 2+ +La 3+ +Y 3+ +Zr 4+ +Ti 4+ )) in the range of 0.000 to 0.100, the refractive index nd in the range of 1.9000 to 2.1500, and the Abbe number vd in the range of 20.0 to 35.0.
[0098] The optical glass has optical properties (nd and νd) that are useful as a material for optical elements. Furthermore, the optical glass does not contain Ta, which is an expensive glass component. 5+ , Gd 3+ , Nb 5+ and W6+ Since the proportion of isopropyl alcohol in the glass is low, this optical glass can contribute to reducing the cost of optical elements.
[0099] In one embodiment, the optical glass is Ti 4+ , Nb 5+ , W 6+ and Bi 3+ The total content may be in the range of 0 to 30 cation %.
[0100] In one embodiment, the optical glass comprises Gd 3+ , Nb 5+ and W 6+ The total content may be in the range of 0 to 8 cation %.
[0101] In one embodiment, the optical glass comprises La 3+ , Gd 3+ and Y 3+ The total content may be in the range of 20 to 60 cation %.
[0102] According to one embodiment, there is provided a glass material for press molding comprising the above optical glass.
[0103] According to one embodiment, there is provided an optical element blank made of the above optical glass.
[0104] The above glass materials for press molding and optical element blanks contain Ta, an expensive glass component. 5+ , Gd 3+ , Nb 5+ and W 6+ Since the optical element is made of the above optical glass in which the proportion of isotopic composition is low, this can contribute to reducing the cost of the optical element.
[0105] According to one embodiment, there is provided an optical element made of the above optical glass.
[0106] The optical elements are made of Ta, an expensive glass component. 5+ , Gd 3+ , Nb 5+ and W 6+Since the optical glass is made of the above optical glass having a low ratio of SiO 2 , it can be manufactured at low cost.
[0107] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. For example, by subjecting the above-mentioned exemplary glass compositions to compositional adjustments as described in the specification, an optical glass according to one aspect of the present invention can be obtained. Furthermore, it is of course possible to arbitrarily combine two or more of the items described in the specification as examples or preferred ranges.
Claims
1. In the glass composition expressed in cation percentage, T 5+ The content is in the range of 0 to 5 cation percent, Zr 4+ The content is in the range of 1 to 15 cation %, A 3+ The content of is 2 cation % or less, S 4+ The content is 2 cation % or more and 20 cation % or less, S 4+ and B 3+ The total content of 4+ +B 3+ ) in the range of 28 to 45 cation percent; La 3+ , Gd 3+ and Y 3+ The total content (La 3+ +Gd 3+ +Y 3+ ) is in the range of 20 to 55 cation %, Ti 4+ , Nb 5+ , W 6+ and Bi 3+ The total content (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ ) in the range of 10 to 28 cation percent; Ti 4+ , Nb 5+ , W 6+ and Bi 3+ Ti relative to the total content 4+ The cationic ratio of the content (Ti 4+ / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ ) is in the range of 0.60 to 1.00, La 3+ , Gd 3+ and Y 3+ Si content relative to the total content 4+ and B 3+ The cation ratio of the total content of (Si 4+ +B 3+ ) / (La 3+ +Gd 3+ +Y 3+ ) is in the range of 0.79 to 0.95, Ti 4+ , Nb 5+ , W 6+ and Bi 3+ Si content relative to the total content 4+ and B 3+ The cation ratio of the total content of (Si 4+ +B 3+ ) / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ ) is in the range of 1.36 to 1.52, Ti 4+ , Nb 5+ , W 6+ and Bi 3+ La relative to the total content 3+ , Gd 3+ and Y 3+ The cation ratio of the total content (La 3+ +Gd 3+ +Y 3+ ) / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ ) is in the range of 1.57 to 5.00, La 3+ and Y 3+ Mg relative to the total content of 2+ , Ca 2+ , Sr 2+ , Ba 2+ and Zn 2+ The cation ratio of the total content ((Mg 2+ +Ca 2+ + Sr 2+ +Ba 2+ +Zn 2+ ) / (La 3+ +Y 3+ ) is in the range of 0.00 to 0.040, S 4+ and B 3+ Mg relative to the total content of 2+ , Ca 2+ , Sr 2+ , Ba 2+ and Zn 2+ Cation ratio ((Mg 2+ +Ca 2+ + Sr 2+ +Ba 2+ +Zn 2+ ) / (Si 4+ +B 3+ ) is in the range of 0.00 to 0.150, S 4+ , B 3+ , Zn 2+ , La 3+ , Y 3+ , Zr 4+ and Ti 4+ Gd relative to the total content 3+ , Nb 5+ and W. 6+ The cationic ratio of the total content ((Gd 3+ +Nb 5+ +W 6+ ) / (Si 4+ +B 3+ +Zn 2+ +La 3+ +Y 3+ + Zr 4+ + Ti 4+ ) is in the range of 0.000 to 0.100, An optical glass having a refractive index nd in the range of 1.9800 to 2.0300, an Abbe number νd in the range of 25.0 to 34.0, and a coloring degree λ70 of 457 nm or less (provided that WO 3 (Excluding optical glasses containing 0.75 mass % or more of
2. In the glass composition expressed in cation percentage, T 5+ The content is in the range of 0 to 5 cation percent, Zr 4+ The content is in the range of 1 to 15 cation %, A 3+ The content of is 2 cation % or less, The content of Si4+ is 2 cation % or more and 20 cation % or less, S 4+ and B 3+ The total content of 4+ +B 3+ ) in the range of 28 to 45 cation percent; La 3+ , Gd 3+ and Y 3+ The total content (La 3+ +Gd 3+ +Y 3+ ) is in the range of 20 to 55 cation %, Ti 4+ , Nb 5+ , W 6+ and Bi 3+ The total content (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ ) in the range of 10 to 28 cation percent; Ti 4+ , Nb 5+ , W 6+ and Bi 3+ Ti relative to the total content 4+ The cationic ratio of the content (Ti 4+ / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ ) is in the range of 0.60 to 1.00, La 3+ , Gd 3+ and Y 3+ Si content relative to the total content 4+ and B 3+ The cation ratio of the total content of (Si 4+ +B 3+ ) / (La 3+ +Gd 3+ +Y 3+ ) is in the range of 0.79 to 0.95, Ti 4+ , Nb 5+ , W 6+ and Bi 3+ Si content relative to the total content 4+ and B 3+ The cation ratio of the total content of (Si 4+ +B 3+ ) / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ ) is in the range of 1.47 to 1.52, Ti 4+ , Nb 5+ , W 6+ and Bi 3+ La relative to the total content 3+ , Gd 3+ and Y 3+ The cation ratio of the total content (La 3+ +Gd 3+ +Y 3+ ) / (Ti 4+ +Nb 5+ +W 6+ +Bi 3+ ) is in the range of 1.57 to 5.00, La 3+ and Y 3+ Mg relative to the total content of 2+ , Ca 2+ , Sr 2+ , Ba 2+ and Zn 2+ The cation ratio of the total content ((Mg 2+ +Ca 2+ + Sr 2+ +Ba 2+ +Zn 2+ ) / (La 3+ +Y 3+ ) is in the range of 0.00 to 0.040, S 4+ and B 3+ Mg relative to the total content of 2+ , Ca 2+ , Sr 2+ , Ba 2+ and Zn 2+ Cation ratio ((Mg 2+ +Ca 2+ + Sr 2+ +Ba 2+ +Zn 2+ ) / (Si 4+ +B 3+ ) is in the range of 0.00 to 0.150, S 4+ , B 3+ , Zn 2+ , La 3+ , Y 3+ , Zr 4+ and Ti 4+ Gd relative to the total content 3+ , Nb 5+ and W. 6+ The cationic ratio of the total content ((Gd 3+ +Nb 5+ +W 6+ ) / (Si 4+ +B 3+ +Zn 2+ +La 3+ +Y 3+ + Zr 4+ + Ti 4+ ) is in the range of 0.000 to 0.100, An optical glass having a refractive index nd in the range of 1.9800 to 2.0300, an Abbe number νd in the range of 25.0 to 34.0, and a coloring degree λ70 of 457 nm or less (provided that Li 2 (Excluding optical glasses containing 0.10 mass % or more of O).
3. G.D. 3+ , Nb 5+ and W. 6+ 3. The optical glass according to claim 1, wherein the total content of is in the range of 0 to 8 cation %.
4. La 3+ , Gd 3+ and Y 3+ Si content relative to the total content 4+ and B 3+ The cation ratio of the total content of (Si 4+ +B 3+ ) / (La 3+ +Gd 3+ +Y 3+ 4. The optical glass according to claim 1, wherein the refractive index is in the range of 0.79 to 0.
94.
5. La 3+ , Gd 3+ and Y 3+ Si content relative to the total content 4+ and B 3+ The cation ratio of the total content of (Si 4+ +B 3+ ) / (La 3+ +Gd 3+ +Y 3+ 5. The optical glass according to claim 1, wherein the refractive index is in the range of 0.79 to 0.
93.
6. S 4+ and B 3+ B relative to the total content of 3+ The cationic ratio of the content (B 3+ / (Si 4+ +B 3+ 6. The optical glass according to claim 1, wherein the refractive index is 0.79 or less.
7. S 4+ and B 3+ B relative to the total content of 3+ The cationic ratio of the content (B 3+ / (Si 4+ +B 3+ 6. The optical glass according to claim 1, wherein the refractive index is 0.78 or less.
8. A glass material for press molding, comprising the optical glass according to any one of claims 1 to 7.
9. An optical element blank comprising the optical glass according to any one of claims 1 to 7.
10. An optical element comprising the optical glass according to any one of claims 1 to 7.
Citation Information
Patent Citations
Optical glass
JP2009203155A
JPP7450105B